Emotope. - Rahmann, Fritz; Schmidt-Wulffen, Stephan; Künstlerhaus Bethanien, Berlin; Büro Berlin, Berlin (Berlin : Büro Berlin, 1988)
Cadieux, Geneviève ; Ecker, Bogomir ; Horndash, Ulrich ; Huber, Stephan ; Ingold, Res ; de Kroon, Harrie ; Kummer, Raimund ; Medve, András ; Nieslony, Boris ; Rahmann, Fritz ; Schläfer, Mike ; Smith, Kiki
Duits
Engels
Emotope, Künstlerhaus Bethanien Berlin, 21. - 27. September 1987 i.s.m. Büro Berlin
boek